Rasa Memiliki terhdap Sekolah: Solusi untuk Mengembangkan Karakter Toleransi Beragama pada Siswa - Saputra, Dedi; Kurniawan, Sandi; Astri, Merita; Ratnasari, Dewi; Syarofah, Syarofah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
In Indonesia, conflicts often occur between ethnicities, religions, races and groups. The survey results show that the proportion of students who are classified as having low or even very low attitudes towards religious tolerance is 30.16%. Based on the results of impartial observations in 2022, there were 25 violations of religious rights or freedom of religion documented by the media, such as refusal to build churches, prohibitions on wearing the veil, and religious blasphemy. The purpose of this article is; first, define and analyze the factors that can influence the religious tolerance of madrasah students through school culture. The author will highlight several factors that can influence students' religious tolerance in madarsahs by integrating them into school culture, which are carried out separately. The factors in question are school atmosphere, student relationships, student-teacher relationships, educational climate and justice, and a sense of belonging. This research uses a quantitative approach with an associative type of research. The data analysis techniques used are descriptive analysis techniques and inferential analysis. Data was obtained from 181 high school students. Data was obtained through the school culture scale and religious tolerance scale. Data were analyzed using regression analysis. Based on the analysis, it was found that the factor that has a significant influence in school culture on students' religious tolerance attitudes at madrasas is a sense of belonging.